RESEPSI ETERNALITAS DALAM KAJIAN TAFSIR AL-JALALAIN DI MADRASAH ALIYAH TAHFIDH AL-QUR'AN UMMUL QURO PAMEKASAN - Ni’mah, Khoirin; -, Mas’ud (El-Waroqoh : Jurnal Ushuluddin dan Filsafat, 2024)
Reception of the Al-Qur'an is a description of how people receive and react to the Al-Qur'an by receiving, responding, utilizing or using it either as a text that contains a written composition of mushaf which has its meaning or a group of words that have a certain meaning. Reception of the Al-Qur'an not only examines the written text, but also reads the conditions of society, where the Al-Qur'an is read, interpreted and practiced in everyday life. In this case, the reception of the Koran generally occurs in Islamic boarding schools, but it is different in that this research occurs in formal education, namely at Madrasah Aliyah Tahfidzil Qur'an Ummul Quro Pamekasan. This research uses qualitative, namely library research and field research. The result of this research is that Madrasah Aliyah Tahfidzil Qur'an Ummul Quro Pamekasan conducted a study of the Al-Jalalayn Tafsir by memorizing it, the reason this tafsir was studied was because the language structure was easy to understand. So that female students can easily memorize the Al-Jalalayn commentary book. One of the unique objectives in this interpretive study is to memorize it. One of the goals is that students and santri are not only good at memorizing but also good at interpreting so that prayer will feel special